Does 1-minute walk test predict results of 6-minute walk test in patients with idiopathic pulmonary fibrosis? - Nunes, Flavia; Pastre, Jean; Brown, Anne W.; Shlobin, Oksana A.; King, Christopher; Weir, Nargues; Nathan, Steven D. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2021)
Background: The six-minute walk test (6MWT) is a readily available tool used to evaluate functional capacity in patients with idiopathic pulmonary fibrosis (IPF). However, it is often logistically challenging to perform in the context of a busy clinical practice. We sought to investigate if the 1MWT distance (1MWD) predicts the 6MWT distance (6MWD), and if an abbreviated walk could accurately predict outcomes in IPF patients. Methods: Baseline demographics and pulmonary function testing of IPF patients evaluated at a tertiary referral center between 2010 and 2017 were collected. 6MWT variables at baseline as well as 1 and 6 minutes were collected. Time to death, lung transplantation, or most recent follow-up was ascertained. Results: There were 177 patients, the majority of whom (80%) were male. The mean age was 67 ± 9 years and mean FVC was 64 ± 18% predicted. Forty eight (27%) patients used oxygen supplementation during the 6MWT. The median 6MWD was 366 meters (IQR: 268-471) while the median 1MWD was 65 meters (IQR: 46-81). Stratified by the median, 89 patients were “High Walkers” based on the 6MWD ≥ 366m (HW6) and 88 patients were “Low Walkers” (LW6). HW6 had a higher FVC% (70 ± 15 vs 57 ± 18, p= 0.001), higher DLCO% (45 ± 12 vs 34 ± 14, p= 0.001) and higher 1MWD (83 ± 28 vs 47 ± 16, m p= 0.001). Median transplant-free survival was better in HW6 vs LW6 (27 ± 16 vs 22 ± 18 months, log rank p= 0.018). There was a strong correlation between the 1MWD and the 6MWD (r= 0.91, Spearman’s correlation, p < 0.0001). Also, the transplant-free survival curves stratified by 1MWD were very similar to the curves for 6MWD, showing a lower survival in the LW1 cohort (log rank p= 0.009). Conclusion: The 1MWD obtained during the first minute of a 6MWD shows a strong correlation to total 6MWD and retains its ability to predict transplant-free survival. 1MWT may serve as a practical substitute for the more cumbersome 6MWT. Our findings require further validation prospectively in larger cohorts of IPF patients.